“Determinación de la duración e intensidad de la latencia en semilla de arroz ( conquista, esperanza, fortaleza, capirona, ferom y moro)” - Julon Tapia, Segundo Ronald (2014)
The present work of research was to determine the effects of drying (natural and artificial) and stored (rest) on the breaking of dormancy, so that way you can get seeds with high germination power and a high percentage germination energy in less time. This study was conducted at the premises of the Regional Committee of Seeds of San Martín, located in the city of Tarapoto to South Latitude 6 º 30 '00 " west longitude and 76 º 29' 00" with an altitude of 330 msnmm. For this work we apply a DCA with factorial arrangements 6x2x5 and 6x1 O, with four trials per treatment, seeds were collected from different fields of farmers in the commercial area of the Lower Mayo and the Amazon region ( the variety of moro - Bagua Grande). The results being reported that Moro ( A6) range with an average of 94.1 % of normal seedlings statistically outperformed other treatments , followed by the conquest (A3), Esperanza ( A2), Fortaleza ( A1), Capirona varieties ( A4) and Feróm (AS), who obtained averages of 81.1%, 37.5 % , 36.2 % , 33.1 % and 19.4% respectively of normal seedlings. With the type of drying factor greater percentage of germination (normal seedlings ) being the type drying oven ( SE) with an average of 56.8 % exceeded the rate statistically sun drying (SS) who scored an average of 37.6 were obtained % . lt is conftrmed that the varieties increased the percentage of normal seedlings according to the increase of drying days, also, it is confirmed that the obtained variety Feróm minor percentages of normal plants with an average of 19.4 % and Moro and varieties Capirona higher average percentages of normal plants with 94.1 % and 81.1 % respectively. Since the Moro ( A6) range with an average of 95.9 % of normal seedlings statistically outperformed other treatments , followed by Fortress (A 1 ) , Capirona (A4 ) , Conquest (A3 ) , Esperanza ( A2) and Feróm varieties ( A5) who obtained averages of 62.3 % , 60.2 % , 50.3 % , 47.5 % and 24.6 % respectively of normal seedlings. Keywords: Latency, dormancy, duration, intensity, variety of rice and normal seedlings.